2008
DOI: 10.1213/ane.0b013e318167cc3a
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Oral Ondansetron Disintegrating Tablets for Prevention of At-Home Emesis in Pediatric Patients After Ear-Nose-Throat Surgery

Abstract: At-home use of ODT may prevent emesis in children during the first 3 days after tonsillectomy in children. Patients who require rescue after prophylactic treatment for nausea and vomiting in the hospital may not respond to prophylactic ondansatron ODT at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…Multiple studies have associated strabismus repair and tonsillectomy with the highest incidences of PONV in children. As such, we chose to dichotomize type of procedure to reflect these previous findings.…”
Section: Discussioncontrasting
confidence: 69%
“…Multiple studies have associated strabismus repair and tonsillectomy with the highest incidences of PONV in children. As such, we chose to dichotomize type of procedure to reflect these previous findings.…”
Section: Discussioncontrasting
confidence: 69%
“…Ondansetron oral disintegrating tablets, which do not require ingestion, at a dose of 4 mg, effectively decrease the incidence of POV [34]. These tablets were also effective for the prevention of at-home emesis during the first 3 days after tonsillectomy [35]. In comparative studies, Furst et al [5], Stene et al [9], Splinter et al [36], and Bolton et al [48] demonstrated that ondansetron 0.1-0.15 mg kg -1 , administered IV after inhalation induction of anesthesia, was more effective than metoclopramide 0.25-0.5 mg kg -1 or droperidol 50-75 mcg kg -1 for the prevention of POV.…”
Section: Serotonin Receptor Antagonistsmentioning
confidence: 99%
“…A recent study in pediatric patients undergoing tonsillectomy or adenoidectomy in an ambulatory setting also reported a lower incidence of PDNV when given five doses of ondansetron ODT over 3 days. 14 Other studies have compared granisetron with other serotonin antagonists for preventing PDNV. White et al 15 compared ondansetron 4 mg iv at the end of the surgery versus granisetron 1 mg po administered prior to induction of anesthesia.…”
Section: Discussionmentioning
confidence: 99%